A rapid action plan to improve diagnosis and management of lipodystrophy syndromes - Fourman, Lindsay T.; Lima, Josivan Gomes; Simha, Vinaya; Cappa, Marco; Alyaarubi, Saif; Montenegro, Renan; Akinci, Baris; Santini, Ferruccio (Frontiers in Endocrinology, 2024)
Lipodystrophy syndromes are rare diseases that can present with a broad range of symptoms. Delays in diagnosis are common, which in turn, may predispose to the development of severe metabolic complications and end-organ damage. Many patients with lipodystrophy syndromes are only diagnosed after significant metabolic abnormalities arise. Prompt action by clinical teams may improve disease outcomes in lipodystrophy syndromes. The aim of the Rapid Action Plan is to serve as a set of recommendations from experts that can support clinicians with limited experience in lipodystrophy syndromes.The Rapid Action Plan was developed using insights gathered through a series of advisory meetings with clinical experts in lipodystrophy syndromes. A skeleton template was used to facilitate interviews. A consensus document was developed, reviewed, and approved by all experts.Lipodystrophy is a clinical diagnosis. The Rapid Action Plan discusses tools that can help diagnose lipodystrophy syndromes. The roles of clinical and family history, physical exam, patient and family member photos, routine blood tests, leptin levels, skinfold measurements, imaging studies, and genetic testing are explored. Additional topics such as communicating the diagnosis to the patients/families and patient referrals are covered. A set of recommendations regarding screening and monitoring for metabolic diseases and end-organ abnormalities is presented. Finally, the treatment of lipodystrophy syndromes is reviewed.The Rapid Action Plan may assist clinical teams with the prompt diagnosis and holistic workup and management of patients with lipodystrophy syndromes, which may improve outcomes for patients with this rare disease.